Numerical investigation on a lithium ion battery thermal management utilizing a serpentine-channel liquid cooling plate exchanger. (October 2019) - Sheng, Lei; Su, Lin; Zhang, Hua; Li, Kang; Fang, Yidong; Ye, Wen; Fang, Yu
Graphical abstract: It is seen from this figure that the maximum temperature rise of the cell module decreases as the increasing rate of fluid flow. The maximum temperature rise of the cell module is under 40 °C and 36 °C respectively since the flow rate is 0.40 × 10 −3 L·s −1 and 1.20 × 10 −3 L·s −1, indicating that increasing flow rate increases the cooling capability of the LCP. Highlights: A new cooling plate is developed for controlling undesirable cell temperature field. Inlet and outlet of cooling plate have big impact on cell temperature distribution. Increasing flow rate decreases cell temperature rise markedly. Cooling plate channel width has weak impact on cell temperature distribution. Channel width has great effect on ratio of power consumption of cooling plate. Abstract: The thermal management for a lithium ion battery cell plays a pivotal role in enhancing the cell performance and reliability for electric vehicles. In this work, a novel serpentine-channel liquid cooling plate with double inlets and outlets is developed for better managing an undesirable temperature distribution of a cell module. With a simplified model for the cell module, numerical analyses are implemented using the software of FloEFD to study effects of flow directions, flow rates and channel widths of the cooling plate on cell temperature distribution under different operating conditions; Likewise, a ratio of power consumption as a non-dimensional number is defined to analyze the hydraulic performance of the developed cooling plate. Results show that locations of the inlet and the outlet as well as flow directions have great impacts on the cell temperature distribution and the ratio of power consumption of the cooling plate. Increasing fluid flow rate substantially decreases the maximum temperature rise of the cell module while it has little effect on the temperature distribution. Moreover, the channel width of the cooling plate has a strong influence on its ratio of power consumption as well as the cell temperature distribution but it has a weak influence on the cell maximum temperature rise. Interestingly, the developed serpentine-channel cooling plate offers one a new method to design a lithium ion battery thermal management system for controlling temperature distribution of a cell module.